RETHINKING TRADITION IN MODERN LIFE - Krisprantono . (Soegijapranata Catholic University, 2005)
In a general sense, tradition is associated with the past that remains integral to us all, while on the other hand modernity look towards the future. Historically, traditions derived from local conditions such as social system, climate, our natural environment and our beliefs about religion and philosophy. However, modernity is more related to our social economic, technology and global information; this influence changes our attitude towards; our heritage and what we should do about it. In the long existence of humanity a new generation appears roughly every twenty five years. In modern time to question is how can tradition survive in the dynamic advancement of modernization? In the West and even in the Eastern culture together with the influence of modernity, traditions and different customs have gradually declined, and in some cases have disappeared. Has tradition and all it stands for been left behind and disappeared?